Pendampingan UMKM Desa Tanggul Wetan dalam Memperoleh Nomor Induk Berusaha (NIB) - Altair, Hafiz Rafi; Dewi, Elsa Firlana; Arifin, Muhammad Pradana; Efendi, Sultan; Prabowo, Gymanastiar Eko; Ningrum, Sefinatur Rahma; Sholihah, Mulimatus; Prayogo, Akmal Alif; Azwar, Ahmad Khoitul; Lindiyana, Lindiyana; Wangi, Rinawati Sekar; Rahmawan, Agus Rizki Dwi; Thohari, Ahmad; Biyuzar, Muhammad (Jumat Ekonomi: Jurnal Pengabdian Masyarakat, 2024)
Creating a Business Identification Number (NIB) has become an important step in efforts to encourage the legality and growth of micro, small and medium enterprises (MSMEs) in Indonesia. However, there are still many MSMEs that do not have adequate understanding of the importance of NIB and related licensing processes. This study aims to analyze the contribution of students in the Real Work Lecture (KKN) program in assisting MSME owners in the process of making NIB. The impact of this assistance includes increasing awareness of business owners about the importance of legality, easier access to financing, training and a wider market. In addition, students of KKN 132 Desa Tanggul Wetan develop communication skills, project management, and application of knowledge in real contexts. Collaboration between students, MSMEs and government agencies also contributes to the acceleration of the licensing process and a better understanding of business licensing regulations. This journal concludes that assistance in making NIB by KKN 132 students at Tanggul Wetan Village has great potential in empowering the local community's economy. Students not only provide practical benefits to MSMEs, but also integrate academic learning with direct application in society. Therefore, NIB assistance by students of KKN 132 Desa Tanggul Wetan is an important step in creating connectivity between the academic world and the business world, as well as contributing to sustainable development. Keywords: NIB Assistance, KKN Students, MSMEs, Business Legality, Economic Empowerment